2019
DOI: 10.3390/su11236728
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Aircraft Taxiing on the Airport Surface with Consideration to Taxiing Conflicts and the Airport Environment

Abstract: High-efficiency taxiing for safe operations is needed by all types of aircraft in busy airports to reduce congestion and lessen fuel consumption and carbon emissions. This task is a challenge in the operation and control of the airport’s surface. Previous studies on the optimization of aircraft taxiing on airport surfaces have rarely integrated waiting constraints on the taxiway into the multi-objective optimization of taxiing time and fuel emissions. Such studies also rarely combine changes to the airport’s e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The implementation process of the NSGA-II algorithm is shown in Figure 4. The adoption of crowding degree and crowding comparison operators not only overcomes the disadvantage of sharing parameters that need to be artificially specified in the NSGA, but also ensures the diversity of the population [23]. The NSGA-II algorithm can be carried out according to the following steps: 1.…”
Section: Solving Methodology 331 Response Surface Methodologymentioning
confidence: 99%
“…The implementation process of the NSGA-II algorithm is shown in Figure 4. The adoption of crowding degree and crowding comparison operators not only overcomes the disadvantage of sharing parameters that need to be artificially specified in the NSGA, but also ensures the diversity of the population [23]. The NSGA-II algorithm can be carried out according to the following steps: 1.…”
Section: Solving Methodology 331 Response Surface Methodologymentioning
confidence: 99%
“…Therefore, the fuel flows and pollutant emission indices must be corrected. Doug and Paynter [23] and Zhang et al [59] reported that the sea level fuel flow of a single engine from aircraft type i when it is at the taxiing state j under the international standard atmospheric (ISA) condition is f ij0 . The correction formulas to convert f ij0 into the practical fuel flow f ij under practical field pressure P and air temperature T at airports are follows: Given that this study focuses on aircraft taxiing, and the taxiing speed is far smaller than the sound velocity, the Mach number M is approximately zero.…”
Section: A Objective Functionmentioning
confidence: 99%
“…The airport environmental changes can influence the fuel consumption for surfacing taxiing of aircraft. Considering the differences of field pressure and air temperature [59], the fuel flow coefficient of aircraft was corrected through the method in Sec. IV.A.…”
Section: Sensitivity Analysis To Airport Environmental Parameters In Multi-objective Route Planningmentioning
confidence: 99%
“…Evertse and Visser [10] designed a realtime airport surface movement planning tool, which was capable of creating conflict-free timed taxiing trajectories for aircraft, while minimizing the total emission of pollutants, fuel usage, departure slot time deviations and taxi time. Zhang et al [11] proposed a multi-objective optimization method for aircraft taxiing based on the airport's environment and traffic conflicts. With the in-depth study of taxiway optimization, in order to simulate the operation of airports, more and more detailed factors were incorporated into aircraft taxiing models.…”
Section: Literature Reviewmentioning
confidence: 99%